Hubungan Asupan Makanan Pada Ibu Hamil Terhadap Kejadian Kekurangan Energi Kronik - Hasnidar; Badariati; Parmin; Sukrang; Magfira (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Chronic Energy Deficiency (CED) is a condition characterized by an imbalance between energy and protein intake, resulting in the body’s nutritional needs not being adequately met. In Central Sulawesi, the prevalence of pregnant women experiencing CED is 22.7%. To determine the relationship between food intake in pregnant women and the incidence of Chronic Energy Deficiency (CED) in the working area of the Bulili Community Health Center. This study used a quantitative design using a cross-sectional approach. The population consisted of all pregnant women who sought antenatal care at the Bulili Community Health Center. A total sampling technique was used, involving 20 pregnant women. Data were collected using a Semi-Quantitative Food Frequency Questionnaire and analyzed using the Chi-Square Test and Fisher’s Exact Test for interpretation. The results of the study revealed that among pregnant women diagnosed with Chronic Energy Deficiency (CED), 6 individuals (40%) had inadequate energy intake, while 9 individuals (60%) had adequate intake. For carbohydrate intake, 8 individuals (53.3%) had inadequate intake, while 7 individuals (46.6%) had adequate intake. For protein intake, 4 individuals (26.6%) had inadequate intake, while 11 individuals (73.3%) had adequate intake. For fat intake, 2 individuals (13.3%) had inadequate intake, while 13 individuals (86.6%) had adequate intake. The Fisher’s Exact Test showed a p-value > 0.005, indicating that there is no relationship between food intake in pregnant women and the incidence of Chronic Energy Deficiency (CED) in the working area of the Bulili Community Health Center.